Los Sorias [The Sorias] and Writing as War: Temporality and Possible Worlds in the Poetics of Alberto Laiseca - Conde De Boeck, José Agustín (Universidad Pedagógica y Tecnológica de Colombia, 2016)
his paper we will analyze the ways in which the representation of war crosses diverse textual levels in Los sorias [The Sorias], Alberto Laiseca’s main novel, and one of the most relevant in Argentine contemporary literature. Adressing the strong cultural importance of the war in Argentine literature, we will examine the relationship between the effect of canonization in Laiseca and the war structure of his “possible worlds”. And we will consider war not just as a literary topic, but as a writing principle and strategy for establishing a particular narrative temporality